Spatial pattern optimization of rural production-living-ecological function based on coupling coordination degree in shallow mountainous areas of Quyang County, Hebei Province, China - Wang, Sen; Tian, Jian; Namaiti, Aihemaiti; Lu, Junmo; Song, Yuanzhen (Frontiers in Ecology and Evolution, 2023)
The shallow mountainous area in Hebei province is a crucial part of the ecological security barrier and regional ecological conservation construction in the Beijing-Tianjin-Hebei (BTH) region. This study take Quyang County as an example, starts from the perspective of PLEF coordinated development, and integrate used multi-source data such as point of interest (POI) and the remote sensing image to build a comprehensive evaluation index system for PLEF by the fine-scale grid. According to the intensity of PLEF and its coupling coordination degree, the functional space type is divided according to the principle of coordinated development and ecological optimization, and the optimal control strategy of the rural functional pattern is proposed by the village scale. The results showed that: (1) The spatial distribution of PLEF in Quyang County is significantly different, and the order of functional intensity is: ecology space (ES) > production space (PS) > living space (LS). (2) The PLEF coupling coordination degree generally presents the spatial distribution characteristics of “low in the north and high in the south”, which is highly related to its topographic features. The high-value areas are mainly spread over southern plains with developed economy and rich ecological resources, while the low-value areas are located in the northern mountains and the central hills. (3) On the grid scale, the PLES pattern is identified as six types: production-living-ecological balance space (PLEBS), production-living space (PLS), production-ecological space (PES), living-ecological space (LES), ES and PS. Among them, the proportion of PLEBS and ES is larger. (4) On the village scale, it is suggested that PLEBS villages further emphasize high-quality coordinated development; ecological function leading optimization type (EFLOT) villages adhere to ecological priorities and ensure the development of ecological space functions; villages with composite functions should combine their own advantages and the spatial characteristics of the surrounding countryside, optimize and control infrastructure configuration, industrial structure, ecological protection and other aspects of classification, overcome shortcomings and improve the coordination of the PLEF. The results can guide for the high-quality coordinated development of territorial space and rural revitalization construction of counties in shallow mountainous areas.